The Phytotoxicity of Palm Oil Mill Effluent, its Degradation and Effect on Plant Growth - Othman, Radziah (1996)
The presence of abundant agricultural residues in Malaysia prompted the need to utilize these wastes to overcome environmental pollution. A large portion of these wastes comes from the oil palm effluent. Palm oil meal (POMeal) has been used as an organic fertilizer to increase growth and yield of several crops. However, application of raw or undecomposed POMeal can also be detrimental to the growth of certain plants. In view of this, the project conducted aimed to study the following aspects: the inhibitory effect of different levels of raw POMeal on growth of vegetables, the effect of decomposition on POMeal phytotoxicity and the degradation of p-coumaric and vanillic acids by Pseudomonas sp. and Penicillium sp. In this study the water-soluble phytotoxic compounds present in raw POMeal will be identified. Results of the glasshouse experiment showed that growth of tomato and spinach was strongly affected by the type (raw or decomposed) and amount of POMeal applied. Growth of both plants was inhibited by application of > 1% raw POMeal. In contrast, application of 1% - 21% decomposed POMeal increased the plant's growth, with maximum dry matter production at 6% POMeal. Increase in shoot dry weight of tomato and spinach given decomposed POMeal was 7 and 178 times respectively. Increase in root dry weights was 1.6 and 62 times respectively, compared to plants given raw POMeal. Soil N, P and K contents, pH and electrical conductivity also increase with increase in PO Meal levels. The phytotoxicity of raw POMeal was reduced when POMeal was decomposed for > 4 weeks.